PANOPTIKON AGAMA SEBAGAI PENOLAKAN DAN KEKERASAN TERHADAP KAUM LGBT DI KOTA MAKASSAR - Agustang, Andi Yosi Adiwisastra Pasca; Agustang, Andi Dody May Putra; Syahrudin, Darma Jaya; Fitriana, Nurthasya (Universitas Negeri Makassar, 2023)
This research aims to analyse 1) The panopticon as a religion that discloses the minds and bodies of dominant actors who reject LGBT people. 2) Forms of violence against LGBT people in the name of religion. 3) The resistance of LGBT people to their rejection. To achieve these goals, this research uses Foucault's Panopticon theory, Lacan's Psychoanalysis theory, Galtung's violence theory and Bulter's Performativity theory. This research method is qualitative-descriptive. Data collection techniques include observation, interviews and documentation and are analysed using data reduction techniques, data presentation, and conclusion drawing. The results of this study show 1) Religion becomes panoptipkon because it is not in accordance with religious values based on Q.S 51:49, Q.S 49:13, Q.S 7:80, Q.S 2 7:54, Q.S 29:28 so that society and mass organisations reject the existence of LGBT people and religion also provides objects of enjoyment such as tranquility, protection, moral and ethical guidelines so that LGBT people are also required to follow religious teachings. 2) Forms of violence against LGBT people include physical and verbal violence, structural violence based on the violence of Indonesian religious culture which is the majority of religious people so that LGBT is considered to disrupt their order even though the act violates article 351 KHUP, 352 KHUP, 359 KHUP, 311 KHUP and human rights. 3) The resistance of LGBT people by performing acts of identity performativity such as wearing clothes according to their gender identification, deconstructing cultural norms such as deconstructing standardised gender language, stereotypes and binaries, collaborating with YLBHI and 23 organisations with the aim of protesting and denouncing the draft regional regulation (raperda) because it is not in accordance with the Universal Declaration of Human Rights.